English-Language Proficiency Requirements for Migration to Canada, Australia, the United Kingdom, and the United States, and the Implications for Language Testing Research - McLeod, Melissa (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2023)
Language proficiency testing has long played a role as both facilitator and barrier in global migration. This paper outlines how Canada and other traditional migrant destination countries use English-language proficiency testing for immigration, asylum and resettlement, and citizenship. It identifies commonalities between these three related areas of migration and the covert values that are often embedded in the required test scores. It identifies different approaches for conducting research under the umbrella of Shohamy’s (2001) Critical Language Testing and concludes with language testing research and advocacy suggestions specific to the Canadian context.